Integrity checking protocol with identity-based proxy signature in mobile cloud computing - Li YAN; Run-hua SHI; Hong ZHONG; Jie CUI; Shun ZHANG; Yan XU (Tongxin xuebao)
Based on provable data possession(PDP)model,a more perfect data integrity checking model for mobile cloud computing was proposed,in which there was an additional proxy party with stronger computing power to help the mobile users to calculate the block tags.Furthermore,for the proposed model,an identity-based proxy signature PDP(IBPS-PDP)protocol was presented.By using identity-based signatures,the system did not need to manage public key certificates and further the users did not need to take the additional computations to verify the other’s certificates yet.Finally,the security of the proposed IBPS-PDP protocol is proved in the random oracle model.